The impact of economic specialization on regional economic development in the European Union: Insights for formation of smart specialization strategy - Giedrė Dzemydaitė (Economies, 2021)
The smart specialization concept was implemented in the EU in 2014, stating that regions have to specify specialization areas for development of innovations. Economic specialization reveals a comparative advantage in that field. However, there are different arguments linking specialization to economic development. This study analyzes these arguments and aims to investigate the impact of economic specialization on regional economic development and to give insights into identifying prospective areas in regional economies. A panel fixed effect estimation of industry-level regional data suggests that economic specialization in broader regional employment, called relative specialization, is ambiguously associated with economic development. Our findings suggest that neither economic specialization nor economic diversity are a clear-cut solution for ensuring economic growth. Economic structure in EU regions differs, and there is no one answer for which approach is better for economic development. Specialization measures, particularly the location quotient, cannot fully capture the dynamics in the industry structure that could be essential for formation of regional development strategy.
Keywords: 330; economic growth; economic specialization; economic structure; EU regions; smart specialization; tradable sectors